Performance of chitosan from mushroom as biocoagulant agent for kaolin and palm oil mill effluent wastewater - Irhayyim, Oday Adnan (2017)
This project aims to investigate the potential use of commercial chitosan produced from mushroom (CMs) as bio-coagulants which are water-soluble chitosan (WSC) and acid-soluble chitosan (ASC) in wastewater treatment. Palm Oil Mill Effluent (POME) is wastewater generated from the palm oil milling industry must be treated properly before being discharged into the environment. The use of inorganic coagulants like alum can potentially lead to the spread of chronic diseases due to the residual content of the coagulants in the treated wastewater. Thus, this study searched for an alternative coagulant using (CMs) for coagulation process. In this study, the optimum condition for synthetic water kaolin treatment when WSC was at pH 8, with a dosage of 10 mg/L, and with almost 100% turbidity removal. While ASC optimum conditions were at pH 11, dosage 10 mg/L and almost 100% turbidity removal. On the other hands, the performances of CMs coagulants as bio-coagulants were compared to aluminum sulphate (alum) coagulant. The results showed that alum gave 93% turbidity removal at optimum pH 4 and with an optimum dosage of 1200 mg/L. The treatment of POME wastewater by using CMs as a bio-coagulant was successfully able to reduce COD with up to 73% in value, 70% of BOD reduction and 99% of TSS removal, whereas alum coagulant resulted in 71% of COD, 65% of BOD reduction and 86% of TSS removal. The second objective of this study was to examine the characterization of the WSC and ASC by using Fourier Transform Infrared (FTIR) analysis, Zeta Potential, and antimicrobial activity. The results of FTIR confirmed the existence of amino groups in the backbone of CMs. The results of Zeta Potential analysis showed that the surface charges for WSC and ASC were 40.46 mV ± 1.01 and +70.24 mV ± 3.69, respectively. The antimicrobial activity analysis showed that ASC is more active than WSC where the concentration used of CMs was 10%. The ASC was active to inhibit microbes within around 7 mm zone which is considered clear zone of inhibition. The estimated cost for treatment using WSC, ASC and alum was RM 5.5, 4.52 and 84 per cubic meter respectively of POME treated wastewater. In conclusion, this study has proven that chitosan mushroom possesses a significant potential to be used as a bio-coagulant for wastewater treatment and also economical.